High-Pressure Physical and Chemical Behaviors of Minerals and Rocks - Dai, Lidong; Hu, Haiying; Jiang, Jianjun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Key Laboratory of High-temperature and High-pressure Study of the Earth's Interior belongs to the Institute of Geochemistry, Chinese Academy of Sciences, China. It is a unique and authoritative key laboratory at the provincial and ministerial levels. The Key High-Pressure Laboratory is primarily focused on the high-temperature and high-pressure experimental sciences, in combination with filed geophysical observation, theoretical calculation and advanced analysis tests in order to explore the chemical composition, cycling structure, geological state, material circulation, etc., of deep Earth. The mainstream research subjects of the Laboratory mainly include: research and development of experimental platforms and measurement techniques at high temperatures and high pressures; high-pressure material synthesis and hot-pressed sintering techniques; physical and chemical characterizations (e.g. electrical conductivity, thermal conductivity, ultrasonic wave velocity, etc.) of minerals and rocks at conditions of high pressure and different oxygen fugacities by virtue of representative high-pressure apparatus, including autoclaves, piston cylinders, multi-anvil presses, diamond anvil cells and shock waves; high-pressure physiochemical behavior and storage states in the geological fluid and melt of deep Earth interior; high-pressure theoretical calculations; and high-pressure applications in the service of national economical and societal development.